Probing the interaction of 1-octyl-3-methylimidazolium containing ionic liquids with small molecules - Gibson, Joshua Simon (2017)
Ionic Liquids (ILs) have drawn a great deal of attention as carbon capture agents, and in order to understand them studies must be performed probing the CO2–IL interaction. Many studies have focused upon measuring the solubility of CO2 within ILs, with fewer studies directly probing the CO2 adsorption environments within the IL. Understanding of the adsorption environments is of fundamental for the use of ILs industrially, if they are to be successfully applied within carbon capture and storage devices. Temperature programmed desorption (TPD) has been used to study the CO2–IL interaction within two ionic liquids; 1-octyl-3-methylimidazolium tetrafluoroborate ([C8C1Im][BF4]) and 1-octyl-3-methylimidazolium bis(trifluoromethylsulfonyl)imide ([C8C1Im][Tf2N]). Experiments were performed utilising low temperature line of sight mass spectrometry (LTLOS MS), ensuring that only species desorbing from the surface are observed. Surfaces were formed through a coadsorption method, where IL was deposited by chemical vapour deposition at a rate of ≈ 1 layer per minute while CO2 was simultaneously leaked into the chamber at pressures between 2×10−8 and 2×10−6 mbar. This study finds that CO2 does not form a monolayer on a gold surface at ≈ 90 K, with no CO2 TPD peak seen for those experiments, showing Edes,CO2 (the activation energy of desorption of CO2) < 24.5 kJ mol−1. When IL and CO2 are coadsorbed the IL is seen to stabilise the CO2, such that a TPD peak for CO2 is seen, with the amount of stabilisation depending upon the IL used. Comparison of experimental TPD curves with calculated TPD profiles, using CO2 states with a range of binding energies, shows that there are multiple CO2 environments within the ILs. The use of TPD allowed the relative populations of these CO2 adsorption environments to be measured, which is not possible using solubility measurements and Henry’s constants, providing insights into the IL–CO2 interaction. CO2 was observed to desorb from sites within the bulk IL, which have activation energies of desorption in the range 24.5 to 43 kJ mol−1. The CO2 was seen to be stabilised most within the [C8C1Im][BF4], giving a stabilisation in Edes of up to 18.5 kJ mol−1. The [C8C1Im][Tf2N] was typically seen to stabilise twice as much CO2 as [C8C1Im][BF4], which is consistent with the experimental Henry’s constants. Further to this a new experimental technique for determining surface structure, utilising high energy X-rays in the total reflection regime, to generate an X-ray standing wave (XSW) and detect the resulting photoelectrons from layered surfaces has been demonstrated. The variable period X-ray standing wave (VPXSW) technique relies on the fact that at low incident angles (typically < 2°) total external reflection of X-rays is observed. The incident and reflected X-rays interact to generate an XSW along the surface normal, with nodes and antinodes at different heights, z, above a reflector for different angles of incidence. By scanning the incident angle of the X-ray from 0° upwards the periodicity of the XSW decreases, resulting in the nodes and antinodes sweeping towards the surface. As this sweeping occurs the nodes and antinodes pass through material adsorbed on the surface of the reflector, and the photoelectron signal fluctuates. Comparing the fluctuations in the measured photoelectron signal to a theoretical model allows surface layering to be detected at larger depths and with a higher information content than with other surface science techniques. This allows distance information, relative to the interfaces between different materials, to be obtained for different chemical species. Data is presented from a surface consisting of the ionic liquid [C8C1Im][BF4] on a Si(001) reflector, held at ≈ 90 K, with a thick IL layer adsorbed on the reflector and a CHCl3 marker layer on top of the IL. Results from the frozen surface indicate a 12 Å layer of CHCl3 and background water had been dosed on top of a 211 Å IL layer. These values agree well with what was expected for this model IL system with a thin marker layer, designed to test the technique. It is therefore shown that VPXSW with photoelectron emission can be used to successfully characterise thin films with thicknesses between 15 Å and ≈ 300 Å with chemical shift specificity, something not possible with current experimental techniques.